Automating crystallographic structure solution and refinement of protein–ligand complexes. (1st January 2014) - Echols, Nathaniel; Moriarty, Nigel W.; Klei, Herbert E.; Afonine, Pavel V.; Bunkóczi, Gábor; Headd, Jeffrey J.; McCoy, Airlie J.; Oeffner, Robert D.; Read, Randy J.; Terwilliger, Thomas C.; Adams, Paul D.
<x xml:space="preserve">Abstract</x> High‐throughput drug‐discovery and mechanistic studies often require the determination of multiple related crystal structures that only differ in the bound ligands, point mutations in the protein sequence and minor conformational changes. If performed manually, solution and refinement requires extensive repetition of the same tasks for each structure. To accelerate this process and minimize manual effort, a pipeline encompassing all stages of ligand building and refinement, starting from integrated and scaled diffraction intensities, has been implemented in Phenix. The resulting system is able to successfully solve and refine large collections of structures in parallel without extensive user intervention prior to the final stages of model completion and validation.